Transverse mode instability - Jauregui, Cesar; Stihler, Christoph; Limpert, Jens (Advances in Optics and Photonics, 2020)
This work presents a review on the effect of transverse mode instability in highpower fiber laser systems and the corresponding investigations led worldwide over the past decade. This paper includes a description of the experimental observations and the physical origin of this effect, as well as some of the proposed mitigation strategies.
CRIS-Team Scopus Importer:2023-04-20